Expansion de Lysiphlebus testaceipes (Creáon)(Hym., Braconidae, Aphidiinae) en el Noreste de la Peninsula Iberica - Pons, X.=700 1 Lumbierres, B.; Stary, P.
(Es, En)
ilus., 17 ref.
Keywords: APHIDIDAE; PARASITOIDES; HUESPEDES; LYSIPHLEBUS TESTACEIPES; CONTROL BIOLOGICO; ESPAÑA